Green Climate Fund (GCF) sebagai Organisasi Internasional Alternatif: Evolusi, Otonomi, dan Peran dalam Tata Kelola Iklim Global - Putri, Ardila (Andalas Institute of International Studies, 2026)
The Green Climate Fund (GCF) was established in 2010 under the framework of the United Nations Framework Convention on Climate Change (UNFCCC) in response to growing demands for a more equitable climate finance mechanism for developing countries. Beyond its role as a financing mechanism, the GCF introduces institutional innovations that challenge conventional models of international organizations through equal representation between developed and developing countries, a country-driven approach, and an explicit commitment to climate justice. This article examines how and in what sense the GCF can be understood as an alternative international organization within contemporary global climate governance. Using a qualitative literature-based approach, informed by theories of international organizations and alternative multilateralism, the article analyzes the GCF's institutional design, legitimacy, and governance arrangements. Limited comparison with conventional international organizations, including the World Bank, IMF, GEF, and UNDP, is employed as an analytical device to clarify the distinctive characteristics of the GCF rather than as the primary focus of the study. The article argues that while the GCF fulfills the formal characteristics of an international organization, it simultaneously introduces institutional innovations that reconfigure representation, participation, and decision-making within global climate governance. Nevertheless, these innovations remain constrained by donor influence, institutional dependencies, and broader structural inequalities. The article concludes that the GCF represents an important institutional experiment that illustrates the ongoing transformation of international organizations in a post-hegemonic era.